2021
DOI: 10.1021/acsapm.1c00775
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Conductivity, Morphology, and Capacitance with Enhanced Antibacterial Properties of Polypyrrole by Acriflavine Hydrochloride

Abstract: In this study, a simple one-step preparation of polypyrrole (PPy) assisted by an organic dye, acriflavine hydrochloride (AF), was investigated. The presence of a dye resulted in the development of PPy nanofibers with the conductivity enhanced up to 14 S cm −1 . The structural analysis by Fourier-transform infrared and Raman spectroscopies confirmed the interaction of the AF with PPy. As far as the electrochemical activity of PPy is concerned, the gravimetric capacitance increased up to 85 F g −1 with the help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The ZOI for 400, 800, and 1200 ppm PFL/CDs-2 was 14, 15, and 17 mm against B. pumilus (Figure a) and 15, 18, and 19 mm against E. coli (Figure d), respectively. It has been previously demonstrated that γ-FeOOH, PPy, CDs, and their composites are effective antimicrobial agents. The antibacterial activity of PFL/CDs-2 composite was further compared with γ-FeOOH, PPy, and CDs at an optimum concentration of 800 ppm, and results suggested that PFL/CDs-2 showed excellent antimicrobial activity against two bacterial pathogens. The ZOI of different materials at 800 ppm was measured to be 13, 11, and 7 mm for γ-FeOOH, CDs, and PPy, respectively, against B. pumilus (Figure b,g), whereas it was 14, 12, and 8 mm for γ-FeOOH, CDs, and PPy respectively against E. coli (Figure e,h).…”
Section: Resultsmentioning
confidence: 98%
“…The ZOI for 400, 800, and 1200 ppm PFL/CDs-2 was 14, 15, and 17 mm against B. pumilus (Figure a) and 15, 18, and 19 mm against E. coli (Figure d), respectively. It has been previously demonstrated that γ-FeOOH, PPy, CDs, and their composites are effective antimicrobial agents. The antibacterial activity of PFL/CDs-2 composite was further compared with γ-FeOOH, PPy, and CDs at an optimum concentration of 800 ppm, and results suggested that PFL/CDs-2 showed excellent antimicrobial activity against two bacterial pathogens. The ZOI of different materials at 800 ppm was measured to be 13, 11, and 7 mm for γ-FeOOH, CDs, and PPy, respectively, against B. pumilus (Figure b,g), whereas it was 14, 12, and 8 mm for γ-FeOOH, CDs, and PPy respectively against E. coli (Figure e,h).…”
Section: Resultsmentioning
confidence: 98%
“…The peaks located at around 287, 406, and 604 cm –1 are ascribed to the E g mode, and the peak at around 659 cm –1 is assigned to the E u mode of α-Fe 2 O 3 , while the peak at 1311 cm –1 is indexed as the α-Fe 2 O 3 second harmonic vibration . After in situ polymerization, two broad peaks appear at 1322 and 1564 cm –1 , originating from the C–C in-ring stretching and the conjugative backbone CC–C ring stretching of PPy, , respectively. In addition, it can be found that the characteristic peaks of Fe 2 O 3 are significantly weakened, which is due to the complete encapsulation of Fe 2 O 3 NFs within the PPy sheaths.…”
Section: Resultsmentioning
confidence: 99%
“…34 Also, enhancement in antibacterial properties of PPy synthesized via chemical polymerization of pyrrole in the presence of acriflavine hydrochloride dye was reported. 46 Further, the antimicrobial activities of PPy or PANI coated fabrics with the help of Ag nanoparticles and PPy aerogels in composition with the cellulose were demonstrated. 47,48 Similarly, functionalized polyaniline was examined for the antibacterial properties against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacteria as reported by Robertson et al 49 They proposed that via hydrogen peroxide production, hydroxyl radicals formation take place which can be responsible for perturbing bacterial cell growth.…”
Section: Properties Required For Antibacterial Activitymentioning
confidence: 96%
“…For instance, a composite of PPy with dextrin exhibited antibacterial activity against the gram‐positive and gram‐negative bacteria 34 . Also, enhancement in antibacterial properties of PPy synthesized via chemical polymerization of pyrrole in the presence of acriflavine hydrochloride dye was reported 46 . Further, the antimicrobial activities of PPy or PANI coated fabrics with the help of Ag nanoparticles and PPy aerogels in composition with the cellulose were demonstrated 47,48 .…”
Section: Importance Of Conducting Polymers In Biomedical Applicationsmentioning
confidence: 98%